School-Based Management and School Heads Management Practicesin Zone III Schools Division of Zambales - Winlyn L. Farin (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This research study aimed to assess the implementation of School-Based Management (SBM) and school heads’ management practices as perceived by teachers in selected elementary schools in Zone III, Division of Zambales during the school year 2021–2022. The study employed a descriptive research design, utilizing a structured questionnaire to collect data from 158 teacher-respondents. Findings revealed that teachers strongly agreed on the effective implementation of SBM, particularly in the dimensions of empowering staff, training staff, introducing schemes for improving quality, integrating various forms of new technology, and promoting continuous professional growth. Similarly, school heads’ management practices were perceived as highly practiced in terms of administrative support, adequacy of physical facilities, and curriculum relevance. Statistical analysis indicated no significant differences in teachers’ perceptions across the dimensions of SBM and management practices, suggesting a consistent understanding and experience among respondents. Based on the findings, an action plan was proposed to further strengthen the continuous implementation of SBM and school heads’ management practices. The study recommends that school heads disseminate the results to improve awareness and application, and encourages future researchers to conduct parallel studies with a wider scope and in-depth exploration to validate and expand upon these findings. Overall, the study underscores the importance of effective management practices in enhancing the quality of elementary education.